Prevalence of Physical and Psychological Violence among Heterosexual Couples - Laura López Angulo; Yenisley Fundora Quintero; Anais Valladares González; Yamila Ramos Rangel; Yanet Blanco Fleites (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
Background: there are few studies at the population level on the prevalence of violence in heterosexual relationships. This study demonstrated the reality of this phenomenon in our context. Objective: to determine the prevalence of psychological and physical violence among heterosexual couples in the city of Cienfuegos in 2010. Methods: a cross-sectional study of adults aged 15 to 74 years was conducted in six health areas. An equal probability sample of 1873 subjects was selected. The variables included psychological and physical violence, sex, age, skin color, marital status, educational level and history of living in troubled homes. The results were processed using SPSS 15.0. Results: prevalence of psychological and physical violence among couples was approximately six out of ten with different frequency levels. Psychological violence rose to 82.3 % and physical violence to 96.3 % when the couple lived together. Women reported being victims of violence from age 35 to 44 and men from age 25 to 34. Seventy point eight percent of couples who had middle school education reported suffering physical violence while 63 % of those with university education reported psychological violence. Fifty-one point eight percent of the study population was victim of physical violence during childhood. Conclusions: prevalence of psychological and physical violence among heterosexual couples in the sample studied in Cienfuegos is higher than the mean in the general population.